PENGARUH PENGGUNAAN INFORMASI AKUNTANSI, MEDIA SOSIAL DAN MODAL TERHADAP KINERJA UMKM DI KEC.KOPANG LOMBOK TENGAH - KARTINI, ENDANG; MIMBAR, LALU; IZRAWATI, IZRAWATI (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to determine whether the use of information, social media and capital has a significant effect both individually and simultaneously on the performance of MSMEs. This type of research is associative, meaning a correlation relationship between independent and dependent. The population was 3,239 MSMEs in Kopang District, Central Lombok, the research sample was 97 respondents. The research results show that the calculated F is 84.986 with a probability of 0.000. (< 0.05), meaning that Accounting Information, Social Media and Capital together influence MSME Performance. The three independent variables included in the regression model are significant because the probability of all three is below 0.05. It can be concluded that the three independent variables influence both partially and simultaneously the performance of MSMEs. If you look at the regression equation, the Constant Value (α) of 1,233 states that if the independent variables are considered constant, then the average MSME performance is 1,233 units assuming the three variables are in a constant or fixed state. One of the three variables whose correlation is not in the same direction as MSME performance is because the value is negative, namely 0.063. Meanwhile, the other 2 variables are social media and capital with respective values of 0.404 and 0.408 (positive), meaning that the relationship is in the same direction as the performance of MSMEs. Furthermore, the R value is 85.6%, this indicates that the correlation relationship between variables is very strong. The Adjusted R Square is 0.724, this means that 72.4% of MSME performance can be explained by variations in the three independent variables. Meanwhile, the remainder (100% - 72.4%) = 27.6%) is explained by other causes outside the model. Standard Error of estimate (SEE) is 0.154. The smaller the SEE value, the more accurate the regression model will be in predicting the dependent variable, namely MSME performance